Quality Service: A Benchmark Setting for Customer Satisfaction in Food Catering Services in Kuala Lumpur Region - Bin Ramli, Mohammad Ammalluddin (Online Journal for TVET Practitioners, 2023)
Intense competition pressures have been brought on by rising customer demand for quality in the food service industry. As a result, they are focusing their strategies on delivering the best possible service, which encourages client satisfaction and loyalty by raising the level of service. In this study, the perception of service quality and its effect on customer satisfaction was investigated by surveying consumers of two distinct catering services in the Kuala Lumpur region. In the study, SERVQUAL was utilized as a questionnaire for the data collection method that was designed to quantify service quality. On 100 instances of valid survey data, regression analysis was performed as part of the analysis. The result shows neither of the two catering services reaches a significant impact on quality service and customer satisfaction. However, the overall mean score is indicative of the fact that caterer A is considered better than caterer B in terms of service quality. The findings demonstrate that customers have the freedom to exercise their right to obtain the services they desire and to choose to do so in order to fulfill their intentions. As a result, ensuring client satisfaction in this tough market where all Malaysian restaurants strive to maintain and retain their services is a high priority for the food service business.